A measure of darkness [compact disc, unabridged] : a novel - Kellerman, Jonathan; Kellerman, Jesse (Kellerman, Jonathan. Clay Edison series., 2018)
Coroner's deputy Clay Edison gets a call in the middle of the night. A body that can't be accounted for is discovered, and the journey to bring her justice leads Clay into a bizarre and seductive world.